Macromol. Rapid Commun. 20/2016. Issue 20 (October 2016) - Freudensprung, Ines; Joe, Daejune; Nietzel, Sven; Vollmer, Doris; Klapper, Markus; Müllen, Klaus
Abstract : Front Cover: Hollow silica particles (HSPs) act as supports for metallocene catalysts to enable ethylene polymerization within their confined geometries. Selective catalyst immobilization inside these uniform HSPs allows for controlled polymer growth and results in spherical polyethylene particles with monomodal size distribution. The fragmented silica shell on the outside, caused by hydraulic forces from polymer growth, can be evidenced microscopically. Further details can be found in the article by I. Freudensprung, D. Joe, S. Nietzel, D. Vollmer, M. Klapper, * and K. Müllen on page 1651.